UTILIZING GRAMMARLY TO IDENTIFY THE ERRORS OF STUDENTS’ RECOUNT TEXT: A CASE STUDY IN MTS CENRANA - Kabirah, Radiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discussed the writing skills of MTs (Madrasah Tsanawiyah) students in recount texts with the assistance of the Grammarly application. Writing was a complex skill, and students often encountered difficulties in grammar, vocabulary, and idea organization. Automated Writing Evaluation (AWE) technology such as Grammarly could provide quick and accurate feedback, thus potentially aiding the learning process. However, most previous studies had only focused on university or vocational school contexts, while the use of Grammarly for junior high school/MTs students in writing recount texts remained understudied. Therefore, this research aimed to fill that gap. The objectives of this study were to identify the types of errors in recount texts written by ninth-grade students at MTs Cenrana and to understand Grammarly's role in enhancing students' motivation in English writing. This research employed a qualitative descriptive method with a case study approach, involving 20 students as subjects for text error analysis, with 10 of them receiving Grammarly treatment and a motivation questionnaire. The findings of the study demonstrated the effectiveness of Grammarly in improving students' recount text writing skills, evidenced by a significant increase in the average score from 41.5 to 80.0 (p=0.004) and a dominant reduction in word errors (40%), sentence structure errors (35%), and spelling and punctuation errors (25%), while student motivation also greatly improved 80% were in the high category due to instant feedback that boosted interest, confidence, independent revision, and tense consistency. This led to the conclusion that Grammarly was effective as both a correction tool and a motivational trigger, with recommendations for its integration into learning and further research to examine long-term impacts and premium features of Grammarly.